BUGUNGI KUNDA JANRLAR EVOLYUTSIYASI VA RIVOJLANISH BOSQICHLARI BORASIDA YANGICHA NAZARIY QARASHLAR - Seitjanova, K. (SCIENCE and SOCIETY, 2023)
In this article speech goes about notion of the genre in music XX centuries, about his (its) development and dug in music creative activity. As well as analysis’s of the scientific conclusions are given about scientifically glance several scientists
Keywords: genre; genesis; style; composer; form; category; vocal; sonata